Characterization of innate immune response to Brucella melitensis infection in goats with permissive or restrictive phenotype for Brucella intramacrophagic growth - Maurizio, Estefanía (2021)
Caprine brucellosis is a chronic, world-wide distributed disease which causes reproductive failure in goats and Brucella melitensis, its causative agent, bears a great zoonotic potential. There is evidence suggesting that some cattle and pigs have an innate ability to resist Brucella infection, but this has not yet been investigated in goats. In this study, we compared caprine macrophages that exhibit extreme restriction and permissiveness to B. melitensis’ intracellular growth in vitro. Monocyte derived macrophages (MDMs) from 110 female goats were cultured and challenged in vitro with B. melitensis 16 M. After initial screening, 18 donor goats were selected based on their macrophages ability to restrict or allow bacterial intracellular growth and some elements of humoral and cellular immunity were studied in depth. MDMs that were able to restrict the pathogen’s intracellular growth showed enhanced bacterial internalization, although there were no differences between groups in the production of reactive oxygen and nitrogen intermediates following 48 h treatment with heat-killed B. melitensis. Moreover, there were no differences between groups in the level of antibodies reacting with keyhole limpet hemocyanin (natural antibodies, NAbs) or with Brucella LPS antigens (cross-reacting antibodies, CrAbs), although a strong positive correlation between individual levels of IgM NAbs and IgM CrAbs was detected. Altogether, these results represent an initial step in understanding innate primary host response to B. melitensis, and deciphering which mechanisms may determine a successful outcome of the infection in goats.